A New Guide Lifter for the Transceiver of USBL - Chai Yongsheng; Min Xiaochen; Liu Mi; Zhang Maoyuan; Wei Shangtao; Wang Changhui*; Liang Mei (Tehnički Vjesnik, 2021)
A new guide lifter has been put forward for the transceiver of Ultra Short Base Line (USBL) with a worm gear reducer applied as self-locking of the lifter and a chain structure applied to drive the sliding shaft moving up and down. The new device is 7500 mm long and connected to the end of the transceiver. Linear motion products are introduced to ensure the shaft unable to rotate and the position measurements are provided by position sensors. A heavy self-sealing sliding bearing, which is 800 mm in length, keeps the shaft running reliably. Then the three-dimensional model is built and the structure parameters of the lifter are calculated. Later, the working process of the lifter is simulated to guarantee the movement parameters meet the request of USBL. Finally, the experiment on the intensity and stiffness of the lifter is carried out via the finite element model of the lifter built in ANSYS with the maximum load conditions and the result has been experimentally verified. This device provides a reliable approach of operating USBL which plays a vitally important role in ocean exploration and the research results are successfully applied to the scientific research vessels of Dayang No. 1 as well as Xiangyanghong No. 9.